PENGARUH ELEKTROLIT TERHADAP KESTABILAN EMULSI LATEKS KARET ALAM - Ali, Muhammad
Natural rubber is a product of plantation and is obtained from the tree of Hevea Brasiliensis as its principal source. The stability of latex is defined as a state in which no coagulation is occured on the conditions studied. In this experiment, the effect of an acid and that of salts on the stability of latex have been studied. The experiment showed that changing pH value from 5 to 8,5 resulted in decreases in viscosity of latex from 37,5x10.-3 poise to 9,87x10.-3 poise, thus decresing the pH value of latex has the effect of increasing the viscosity. This increase in viscosity can also be resulted from the effect of calcium chloride or alumunium sulphate. At calcium chloride consentrations from 9x10.-4 to 45x10.-4 mol L.-1, the viscosity of 10,48x10.-2 to 39,22x10.-2 poise were obtained. While at alumunium sulphate consentrations from 2,92x10.-4 to 14,60x10.-4 mol L.-1 the viscosity of 13,20x10.-2 to 40,20x10.-2 poise were recorded. Zeta potential measurement showed that latex has potential range between 15 and 90 mV. The movement of latex particles to anode show that they have negative charges. This experiment show that acid as well as salts decrease zeta potential of latex changing pH value from 5 to 8,5 resulted in increase in zeta potential from 15,5 mV to 86,06 mV. The addition of calcium chloride to latex changed its potential from 18,33 mV to 61,93 mV. While the addition of alumunium sulphate caused its zeta potential to change from 16,5 mV to 42,70 mV. by soap titration method whith lauryl sulphate,and keeping the conditions during the titration exactly the same as in the measurement of zeta potential and that of viscosity, the following conclusions can be drawn concerning the offect of formic acid, calcium chloride or alumunium sulphate on the measurement of particle size; The addition of formic acid gave the mean value of surface diameter (dvs) from 0,31 u to 1,14 u or spesific surface area (S) from 19,57x10.4 cm² to 5,26x10.4 cm². With calcium chloride dvs value of 0,36 u to 0,98 u or S value from 6,13x10.4 cm² to 16,64x10.4 cm² were obtained, while the addition of alumunium sulphate gave dvs value from 0,35 u to 0,94 u or S value from 6,38x10.4 cm² to 17,35x10.4 cm². At critical value of pH 5 the particle size is still in the limits of size of colloid particle (0,1-0,001 u)(5). The same results were also obtained on treating the latex with calcium chloride or with alumunium sulphate. As in zeta potential and viscosity measurements, electrolytes having valence of 3 give greater effects on particle size than electrolytes having valence of 2 with the same consentrations. Because the critical state has a similar meaning to coagulation, it can be said that coagulation number of electrolyte with valency of 2 compared with electrolyte with valency of 3 is in the proportion of 3 to 1.